Analysis and design of triangular symmetric double ridged waveguide by finite element method - CHEN Xiao-qiang1; REN En-en1; LU Mai2; WANG Lei1 (Tongxin xuebao)
The characteristic parameters of novel triangular symmetric double ridged waveguide（TSDRW） have been analyzed and calculated by employing finite element method.Dependence of the cutoff wavelength,single-mode band-width,field pattern,characteristic impedance,attenuation constant and power-handling capacity on the varied ridge di-mensions have been investigated in details.Compared with the conventional rectangular ridged waveguide,TSDRW pro-vides short cutoff wavelength,narrow single-mode bandwidth,low power-handling capacity,high attenuation and large characteristic impedance.The TSDRW structure can be developed as the microwave filter with narrow-band operation.Numerical results provide extensive design data for the application of TSDRW in microwave systems.